MENGUATKAN KEPEDULIAN SOSIAL SISWA MELALUI PENDIDIKAN NONFORMAL - Wiyesi, Andriyani; Lan, Yap Fu (CREDENDUM: Jurnal Pendidikan Agama, 2023)
This study aims to determine and describe the development of social awareness of students at RPTRA Komarudin, supporting and inhibiting factors, methods for developing social awareness, and teacher efforts in dealing with students who do not yet have social awareness. This study is a qualitative study with data collection techniques using observation and interviews. The research instrument was designed based on the theory of Samani and Hariyanto which contains nine indicators of social awareness, namely: (1) behaving politely, (2) being polite, (3) being tolerant, (4) not hurting others, (5) not taking advantage of others, (6) working together, (7) being involved in community activities, (8) loving fellow human beings and other living things, and (9) loving peace. The results of the study showed five indicators of social awareness that had been carried out by students (indicators 1, 2, 6, 8, and 9). Efforts to develop students' social awareness were carried out through teaching and providing motivation and examples. The final result of this study is a recommendation for RPTRA Komarudin to improve efforts to develop students' social awareness in the community.